Autoreactive B cells recruited to lungs by silica exposure contribute to local autoantibody production in autoimmune-prone BXSB and B cell receptor transgenic mice - Fee, Lanette; Kumar, Advika; Tighe, Robert M.; Foster, Mary H. (Frontiers in Immunology, 2022)
Occupational exposure to inhaled crystalline silica dust (cSiO2) is linked to systemic lupus erythematosus, rheumatoid arthritis, systemic sclerosis, and anti-neutrophil cytoplasmic autoantibody vasculitis. Each disease has a characteristic autoantibody profile used in diagnosis and implicated in pathogenesis. A role for cSiO2 in modulating humoral autoimmunity in vivo is supported by findings in mice, where respirable cSiO2 induces ectopic lymphoid structures as well as inflammation in exposed lungs across genetically diverse backgrounds. In lupus-prone mice cSiO2 exposure also leads to early onset autoantibody production and accelerated disease. Elevated autoantibody levels in bronchoalveolar lavage fluid (BALF) and lung transcriptome analysis suggest that the lung is a hub of cSiO2-evoked autoimmune activity. However, mechanisms by which cSiO2 and lung microenvironments interact to promote autoantibody production remain unclear. We previously demonstrated elevated anti-DNA Ig in BALF but not in lung cell cultures from cSiO2-exposed C57BL/6 mice, suggesting that BALF autoantibodies did not arise locally in this non-autoimmune strain. Autoantibodies were also elevated in BALF of cSiO2-exposed lupus-prone BXSB mice. In this report we test the hypothesis that dysregulated autoreactive B cells recruited to cSiO2-exposed lungs in the context of autoimmune predisposition contribute to local autoantibody production. We found that anti-DNA and anti-myeloperoxidase (MPO) Ig were significantly elevated in cultures of TLR ligand-stimulated lung cells from cSiO2-exposed BXSB mice. To further explore the impact of strain genetic susceptibility versus B cell intrinsic dysfunction on cSiO2-recruited B cell fate, we used an anti-basement membrane autoantibody transgenic (autoAb Tg) mouse line termed M7. In M7 mice, autoAb Tg B cells are aberrantly regulated and escape from tolerance on the C57BL/6 background. Exposure to cSiO2 elicited prominent pulmonary B cell and T cell aggregates and autoAb Tg Ig were readily detected in lung cell culture supernatants. Taken together, diverse disease-relevant autoreactive B cells, including cells specific for DNA, MPO, and basement membrane, are recruited to lung ectopic lymphoid aggregates in response to cSiO2 instillation. B cells that escape tolerance can contribute to local autoantibody production. Our demonstration of significantly enhanced autoantibody induction by TLR ligands further suggests that a coordinated environmental co-exposure can magnify autoimmune vulnerability.